Association Of Gender And Caries Experience Based On Dmft Index - Retrospective Analysis Of Patient Records - K., MONISHA.; LEELAVATHI, L.; K., ARAVIND. (The journal of contemporary issues in business and government, 2021)
Dental caries is a very complex disease affecting people worldwide. Its incidence is witnessing a decline in developed countries due to proper availability of fluoride products, better oral health services, and awareness regarding etiology of caries. To apply measures which can prevent or control caries , DMFT indexes are used which is one of the most important quantitative factors, in measuring tooth caries level of an individual.The aim of the present study was to determine association between DMFT score and gender in adult patients who reported to a Private hospital in Chennai. An institutional record based study was done to assess the association between gender and caries experience in outpatients.The study was carried out on an one-year period, (June 2019 to April 2020) on a total of 4643 patients ( 2541 males and 2102 females) records which were analysed for DMFT index. The results obtained were analysed through SPSS software. From the results obtained the DMFT score of 8-14 was found highest among 44.2 % patients. DMFT score of 0-7 was highest in males compared to females. DMFT scores of 8-14, 15-21 and 22- 28 were highest in females compared to males. (p value = >0.05).The study concludes that higher caries experience was found among females than males but the study was insignificant..